Dyslipidemia and nutritional status in patients HIV positive with Syndrome Lipodystrophy. - Isameriliam Rosaulem Pereira da Silva; Rosa Maria Dias; Andreza de Nazaré Leão Mendes; Rosana Maria Feio Libonati; Claudia Daniele Tavares Dutra (Universidade de Santa Cruz do Sul, 2014)
Backgound and Objectives: Lipodystrophy in HIV is adversely affect the antiretroviral therapy (HAART), characterized by redistribution of body fat, as well as metabolic changes related to lipid profile, risk factor associated with increased cardiovascular disease. This study aimed study HIV-positive patients with lipodystrophy and its association with dyslipidemia to and nutritional status. Methods: This is an analytical cross-sectional study conducted from January 2010 to March 2012. The sample consisted of patients with positive serology for HIV, undergoing HAART presenting dyslipidemia and lipodystrophy syndrome. Data were collected anthropometric, biochemical, clinical and sociodemographic. Results: 79 patients were studied, with a mean age of 44.2 years (±9.4), 62% male. Most had more than 9 years of education (68.3%) and lived with 1 3 minimum wages (40.8%). The most frequent type of marriage was not stable (91.1%). Among the clinical forms of lipodystrophy, the joint was the most prevalent (49.9%). It was observed that 65.8% of patients had nutritional status of eutrophic. Regarding dyslipidemia, it was found that 43.0% of patients had hypercholesterolemia, hypertriglyceridemia 63.3%, 24.0% low HDL-c and 6.3% had high LDL-c. Regarding the association between clinical forms of lipodystrophy and dyslipidemia and nutritional status, was observed an association only with nutritional status (p=0, 0003). Conclusion: The mixed lipodystrophy was the most frequent clinical form and overweight was present in 1 out of 5 patients. Most patients had hypertriglyceridemia, more frequently in men. Clinical forms of lipodystrophy not associated with the types of dyslipidemia, however were associated with nutritional status. KEYWORDS: Dyslipidemia. Lipodystrophy. Nutritional State. HIV.